Time-Series Estimation of Structural Import Demand Equations : A Cross-Country Analysis - Senhadji, Abdelhak (IMF Working Papers; Working Paper ;, 1997)
This paper derives a structural import demand equation and estimates it for a large number of countries, using recent time series techniques that address the problem of nonstationarity. Because the statistical properties of the different estimators have been derived only asymptotically, econometric theory does not offer any guidance when it comes to comparing different estimators in small samples. Consequently, the paper derives the small-sample properties of both the ordinary-least-squares (OLS) and the fully-modified (FM) estimators using Monte Carlo methods. It is shown that FM dominates OLS for both the short- and long-run elasticities.